2019
DOI: 10.1101/619924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor GBF1 participates in rotavirus replication

Abstract: 19Cellular and viral factors participate in the replication cycle of rotavirus. We report that the 20 guanine nucleotide exchange factor GBF1, which activates the small GTPase Arf1 to induce 21 COPI transport processes, is required for rotavirus replication since knocking down GBF1 22 3 IMPORTANCE 40 Rotavirus, a member of the family Reoviridae, is the major cause of severe diarrhea in 41 children and young animals worldwide. Despite the significant advances in the 42 characterization of the biology of this vi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 88 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…The identification of major cellular events regulated by garz/ GBF1 27-29, [47][48][49] has targeted such molecules for health and disease studies 18 . Recently, it has been shown that siRNA knockdown of GBF1 causes intracellular APP accumulation in primary cortical neurons; overexpression of GBF1 contributes to APP trafficking and is dependent on its GEF activity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of major cellular events regulated by garz/ GBF1 27-29, [47][48][49] has targeted such molecules for health and disease studies 18 . Recently, it has been shown that siRNA knockdown of GBF1 causes intracellular APP accumulation in primary cortical neurons; overexpression of GBF1 contributes to APP trafficking and is dependent on its GEF activity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The identification of major cellular events regulated by garz/GBF1 27-29, [47][48][49] has targeted such molecules for health and disease studies 18 . Recently, it has been shown that siRNA knockdown of GBF1 causes intracellular Amyloid Precursor Protein (APP) accumulation in primary cortical neurons; overexpression of GBF1 contributes to APP trafficking and is dependent on its GEF activity 50 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of genome-wide RNAi screens has shown that the vesicle transport mediated by the COPI/Arf1 machinery is relevant for virus replication, since knocking down the expression of some of the proteins that integrate such machinery significantly impairs the yield of rotavirus progeny [ 141 , 142 ]; similar results are obtained when the vesicle transport is inhibited by BFA treatment of rotavirus-infected cells [ 76 , 143 ]. This inhibition is related to the activity of GBF1, since interfering specifically with this factor by GCA, or depletion of this nucleotide exchange factor by RNAi, significantly reduced the production of new viral infectious particles [ 76 ]. In addition, the block in the production of infectious virus was associated with the assembly of the virus surface proteins VP7 and VP4, since both BFA and GCA block the assembly of the viral surface proteins onto DLPs, preventing the production of mature infectious TLPs [ 76 ].…”
Section: Double-stranded Rna Virusesmentioning
confidence: 99%
“…This inhibition is related to the activity of GBF1, since interfering specifically with this factor by GCA, or depletion of this nucleotide exchange factor by RNAi, significantly reduced the production of new viral infectious particles [ 76 ]. In addition, the block in the production of infectious virus was associated with the assembly of the virus surface proteins VP7 and VP4, since both BFA and GCA block the assembly of the viral surface proteins onto DLPs, preventing the production of mature infectious TLPs [ 76 ]. The restriction in the assembly of TLPs was shown to be the result of a defective trimerization of VP7, required for its assembly onto DLPs, rather than a block in the budding of DLPs into the ER lumen.…”
Section: Double-stranded Rna Virusesmentioning
confidence: 99%
See 1 more Smart Citation